(untitled) (London Journal of Engineering Research, 2024)
The use of welds with dissimilar characteristics is applied when it is necessary to join two materials that are considered metallurgically, mechanically, and chemically different. This study aims to understand the metallurgical effects on dissimilar joints between a low-carbon steel SAE 1015 and the AWS A5.36 E110C-MG low-alloy welding wire and the AWS A5.18 ER70S-6 low-carbon steel electrode, using the Gas Metal Arc Welding (GMAW) process. To characterize the bonding line between the materials, the chemical composition of both metals was evaluated through optical emission spectroscopy, and metallurgical characterization was carried out using an optical microscope, also assessing the Vickers microhardness. In order to map the thermal behavior, thermographic images were obtained during the welding process. In the microstructural evaluation of the bonding zone between the base material and the deposited material, the presence of Widmansttten ferrite was observed, with a refined grain size microstructure in the weld region, which explains the increase in microhardness by approximately 24%.